Pengaruh Bias Gender dalam Komunikasi Keluarga terhadap Toxic Masculinity - Febi Salsabila Adhani; Maya Oktaviani; Tarma Tarma (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the influence of gender bias in family communication on toxic masculinity among adolescent boys. The research employed an empirical quantitative approach with an associative design involving male students aged 12–15 years at SMP Negeri 74 Jakarta. Data were collected through structured questionnaires distributed using Google Forms and analyzed using binary logistic regression. Gender bias in family communication was measured through dimensions of marginalization, subordination, stereotypes, violence, and double burden, while toxic masculinity was assessed through threat and boost dimensions. The findings indicate that gender bias in family communication significantly affects toxic masculinity among adolescents, with a Nagelkerke R Square value of 0.719. The results demonstrate that patriarchal communication patterns within families contribute to the reproduction of rigid masculine norms among adolescent boys. Family based gender awareness is therefore essential to support healthier and more inclusive adolescent social development.